Exploring Space-Time Fixity about Activity Types and Mode Choice - Mahmudah, Amirotul M. H.; Budiarto, Arif; Dharmowijyo, Dimas B. E.; Joewono, Tri Basuki; Asmaningrum, Tri Hardiyanti (Universitas Islam Sultan Agung Semarang, 2025)
Space-time fixity and flexibility of activity are essential for understanding how space-time constraints influence accessibility and mobility in daily life. Reducing these constraints helps improve quality of life and solve urban problems like traffic jams. Thus, these concepts are vital not only in academia but also in transportation and travel behavior studies. This research explores how activity type and mode choice influence space-time fixity. Descriptive statistic were used to profile respondents and their activities, while bivariate analysis looked at the relationship between mode choice and activity type in terms of space-time fixity. Specifically, mode choices—such as non-motorized, motorcycle, car, public transport, and ride-sourcing—and various out-of-home activities like travel, working/studying, socializing, and grocery shopping. Daily activity data from the Surakarta agglomeration area during the COVID-19 pandemic in 2021 was collected for this study. This study finds that space fixity occurs more often than time fixity, and activities' average level of space and time fixity is fairly flexible. The time fixity pattern for mode choices in out-of-home activities is similar for most activities, except socializing. In contrast, space fixity patterns differ among out-of- home activities. Working/studying outside the home shows the highest time and space fixity across all modes. Research indicates that a score of 6.0 on a 7-point Likert scale represents the highest space-time fixity. This score applies to those who mainly use public transport, with time fixity linked to travel activity and space fixity to out-of-home working/studying activity. The implications of these results on urban planning are discussed.